Growth suppression of Friend virus-transformed erythroleukemia cells by p53 protein is accompanied by hemoglobin production and is sensitive to erythropoietin. - Johnson, P (1993)
The murine allele temperature-sensitive (ts) p53Val-135 encodes a ts p53 protein that behaves as a mutant polypeptide at 37 degrees C and as a wild-type polypeptide at 32 degrees C. This ts allele was introduced into the p53 nonproducer Friend erythroleukemia cell line DP16-1. The DP16-1 cell line was derived from the spleen cells of a mouse infected with the polycythemia strain of Friend virus, and like other erythroleukemia cell lines transformed by this virus, it grows independently of erythropoietin, likely because of expression of the viral gp55 protein which binds to and activates the erythropoietin receptor. When incubated at 32 degrees C, DP16-1 cells expressing ts p53Val-135 protein, arrested in the G0/G1 phase of the cell cycle, rapidly lost viability and expressed hemoglobin, a marker of erythroid differentiation. Erythropoietin had a striking effect on p53Val-135-expressing cells at 32 degrees C by prolonging their survival and diminishing the extent of hemoglobin production. This response to erythropoietin was not accompanied by down-regulation of viral gp55 protein.